Electrode, battery, and method for manufacturing electrode
The electrode structure with varying binder coating rates in its layers addresses the issue of capacity loss and resistance increase in lithium-ion batteries at high temperatures by maintaining cohesion and conductivity.
Patent Information
- Application Number
- JP2022177244
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-11-04
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2042-11-04
AI Technical Summary
The capacity maintenance rate of lithium-ion secondary batteries decreases and resistance increases when stored at high temperatures due to binder swelling in the electrode layer, which affects the cohesion and conductivity of the collector and electrode layer.
The electrode structure comprises a first electrode layer with a high binder coating rate and a second electrode layer with a lower binder coating rate, using specific binders and active materials to maintain cohesion and conductivity, respectively.
This structure effectively suppresses the decrease in capacity maintenance rate and the increase in resistance at high temperatures by balancing binder coverage in the electrode layers.
Smart Images

Figure 0007626122000002 
Figure 0007626122000003 
Figure 0007626122000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to electrodes, batteries, and methods of making electrodes. [Background technology]
[0002] In recent years, with the rapid spread of electronic devices such as personal computers and mobile phones, the development of batteries to be used as power sources for these devices is progressing. In the automotive industry, the development of batteries to be used in hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs) and battery electric vehicles (BEVs) is also progressing. Among various types of batteries, lithium-ion secondary batteries have the advantage of having a high energy density.
[0003] A battery, such as a lithium ion secondary battery, usually has a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode. The positive electrode usually has a positive electrode current collector and a positive electrode layer containing a positive electrode active material. The negative electrode usually has a negative electrode current collector and a negative electrode layer containing a negative electrode active material.
[0004] Patent Document 1 discloses a multilayer electrode structure in which electrode layers each having at least a binder made of a polymeric substance and an electrode material are laminated in multiple layers on a current collector, the multilayer electrode structure being characterized in that a first electrode layer arranged in contact with the current collector and a second electrode layer arranged on the first electrode layer have different material compositions or different compounding ratios.
[0005] Patent Document 2 discloses a separator interposed between a positive electrode and a negative electrode of a lithium battery, which includes a substrate and a first layer and a second layer disposed on one surface of the substrate, and which uses different binder types for the first layer and the second layer.
[0006] Patent Document 3 discloses a method for manufacturing an electrode for a secondary battery, which includes a step of applying a first layer slurry to the surface of a current collector, a step of applying a second layer slurry onto the first layer slurry before the first layer slurry is dried, and a step of drying the first layer slurry and the second layer slurry after applying the first layer slurry and the second layer slurry to obtain a laminated structure in which the first layer and the second layer are laminated in this order on the current collector, and it is disclosed that the first layer is an active material layer and the second layer is an insulating layer that does not contain active material, and that the viscosity of the slurry differs depending on the type of binder.
[0007] Patent Document 4 discloses an electrode for a lithium ion secondary battery having a current collector and an electrode layer, the electrode layer consisting of a first electrode layer and a second electrode layer having a binder resin concentration higher than the binder resin concentration of the first electrode layer. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2001-307716 A [Patent Document 2] JP 2020-136276 A [Patent Document 3] JP 2019-096501 A [Patent Document 4] International Publication No. 2011 / 142083 Summary of the Invention [Problem to be solved by the invention]
[0009] As a result of intensive research, the present inventors have found that when a battery is stored at a high temperature (for example, 60°C), the capacity retention rate may decrease. This is believed to be because, during high-temperature storage, the binder in the electrode layer swells with the electrolyte, reducing the binding strength of the electrode layer, thereby reducing the electronic conductivity at the interface between the current collector and the electrode layer. On the other hand, when the amount of binder in the electrode layer is increased, the decrease in the capacity retention rate during high-temperature storage is suppressed, but the resistance increase rate during high-temperature storage increases.
[0010] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide an electrode that can suppress an increase in the resistance increase rate while suppressing a decrease in capacity retention rate during high-temperature storage. [Means for solving the problem]
[0011] [1] An electrode for use in a battery, comprising: the electrode includes a current collector, a first electrode layer disposed on the current collector, and a second electrode layer disposed on the first electrode layer; the first electrode layer has a first active material and a first binder covering a surface of the first active material, the second electrode layer has a second active material and a second binder coating a surface of the second active material, An electrode, in which, when a coverage rate of the first binder with respect to the first active material is C1 (%) and a coverage rate of the second binder with respect to the second active material is C2 (%), C1 is greater than C2.
[0012] [2] The electrode according to [1], wherein C1 is greater than 50% and C2 is 50% or less.
[0013] [3] The electrode according to [1] or [2], wherein the difference between C1 and C2 is 30% or more.
[0014] [4] The electrode according to any one of [1] to [3], wherein the first binder and the second binder are fluorine-containing binders.
[0015] [5] The electrode according to any one of [1] to [4], wherein the first binder and the second binder have the same composition.
[0016] [6] The electrode according to any one of [1] to [5], wherein the first active material and the second active material are a lithium transition metal composite oxide.
[0017] [7] The electrode according to any one of [1] to [6], wherein the first active material and the second active material have the same composition.
[0018] [8] the first electrode layer contains a first composite in which the first binder and a first conductive material are dispersed on a surface of the first active material, The electrode according to any one of [1] to [7], wherein the second electrode layer contains a second composite in which the second binder and a second conductive material are dispersed on a surface of the second active material.
[0019] [9] A battery having a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode, A battery, wherein at least one of the positive electrode and the negative electrode is the electrode according to any one of [1] to [8].
[0020]
[10] The battery according to [9], wherein the battery is a lithium ion battery.
[0021]
[11] A method for producing an electrode for use in a battery, comprising the steps of: a first film-forming step of forming a first electrode layer on a current collector by a dry method using a first electrode mixture containing a first active material and a first binder that coats a surface of the first active material; a second film-forming step of forming a second electrode layer on the first electrode layer by a dry method using a second electrode mixture containing a second active material and a second binder that coats a surface of the second active material; having A method for manufacturing an electrode, wherein, when a coverage rate of the first binder to the first active material is C1 (%) and a coverage rate of the second binder to the second active material is C2 (%), C1 is greater than C2. Effect of the Invention
[0022] The electrode according to the present disclosure exhibits the effect of being able to suppress an increase in the rate of increase in resistance while suppressing a decrease in the capacity retention rate during high-temperature storage. [Brief description of the drawings]
[0023] [Figure 1] 1 is a schematic cross-sectional view illustrating an electrode according to the present disclosure. [Diagram 2] 1A and 1B are schematic plan and cross-sectional views illustrating electrodes according to the present disclosure. [Diagram 3] FIG. 1 is a schematic cross-sectional view illustrating a battery according to the present disclosure. [Figure 4] FIG. 1 is a flow diagram illustrating a method for manufacturing an electrode in the present disclosure. [Diagram 5] 11 is a binarized image illustrating a method for calculating a binder coverage rate. [Figure 6] 1 is a graph showing the relationship between binder coverage and powder resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Hereinafter, the embodiments of the present disclosure will be described in detail with reference to the drawings. Each of the drawings shown below is a schematic illustration, and the size and shape of each part are appropriately exaggerated to facilitate understanding. In addition, in this specification, when expressing an aspect in which another member is arranged relative to a certain member, the term "above" or "below" is used, unless otherwise specified, it includes both a case in which another member is arranged directly above or below a certain member so as to be in contact with the certain member, and a case in which another member is arranged above or below a certain member via another member.
[0025] A. Electrode FIG. 1 is an explanatory diagram for explaining an electrode in the present disclosure. The electrode 10 shown in FIG. 1 has a current collector 1, a first electrode layer 2a arranged on the current collector 1, and a second electrode layer 2b arranged on the first electrode layer 2a. The first electrode layer 2a has a first active material and a first binder that covers the surface of the first active material. The second electrode layer 2b has a second active material and a second binder that covers the surface of the second active material. In the present disclosure, when the coverage of the first binder with respect to the first active material is C1 (%) and the coverage of the second binder with respect to the second active material is C2 (%), C1 is larger than C2.
[0026] According to the present disclosure, since the coverage C1 of the first binder is greater than the coverage C2 of the second binder, it is possible to suppress the increase in the resistance increase rate while suppressing the decrease in the capacity retention rate during high-temperature storage. As described above, when the battery is stored at a high temperature (for example, 60°C), the capacity retention rate may decrease. This is considered to be because the binder in the electrode layer swells with the electrolyte during high-temperature storage, and the binding force of the electrode layer decreases, resulting in a decrease in the electronic conductivity of the interface between the current collector and the electrode layer. On the other hand, when the amount of binder in the electrode layer is increased, the decrease in the capacity retention rate during high-temperature storage is suppressed, but the resistance increase rate during high-temperature storage increases.
[0027] In contrast, in the present disclosure, the coverage C1 of the first binder in the first electrode layer is relatively high, so that the first electrode layer and the current collector are less likely to peel off, and as a result, the decrease in the capacity retention rate during high-temperature storage is suppressed. At the same time, the coverage C2 of the second binder in the second electrode layer is relatively low, so that the increase in the resistance increase rate during high-temperature storage is suppressed. In other words, both the improvement of the capacity retention rate and the suppression of the resistance increase rate can be achieved.
[0028] The coverage C1 of the first binder with respect to the first active material is, for example, greater than 50%, and may be 60% or more, or 70% or more. If the coverage C1 is too small, peeling between the first electrode layer and the current collector is likely to occur. On the other hand, the coverage C1 is, for example, 95% or less. If the coverage C1 is too large, ionic conduction and electronic conduction to the first active material may be inhibited. Details of the method for calculating the coverage will be described in detail in the examples described later. In addition to the binarization process described later, the coverage can also be obtained by, for example, SEM-EDX.
[0029] The coverage C1 of the first binder with respect to the first active material is, for example, greater than 50%, and may be 60% or more, or 70% or more. If the coverage C1 is too small, peeling between the first electrode layer and the current collector is likely to occur. On the other hand, the coverage C1 is, for example, 95% or less. If the coverage C1 is too large, ionic conduction and electronic conduction to the first active material may be inhibited.
[0030] The coverage C2 of the second binder with respect to the second active material is, for example, 50% or less, and may be 45% or less, or may be 35% or less. If the coverage C2 is too large, the resistance is likely to be large. On the other hand, the coverage C2 is, for example, 10% or more, and may be 20% or more. If the coverage C2 is too small, peeling between the first electrode layer and the second electrode layer is likely to occur.
[0031] The difference between the coverage C1 and the coverage C2 is, for example, 15% or more, may be 30% or more, or may be 45% or more.
[0032] 1.First electrode layer The first electrode layer is disposed between the current collector and the second electrode layer, and has a first active material and a first binder that coats a surface of the first active material.
[0033] (1) First binder The first electrode layer contains a first binder. The first binder is usually a polymer. Typical examples of the first binder include fluorine-containing binders (fluoride-based binders) such as polyvinylidene fluoride (PVDF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene (PTFE), and fluorine rubber.
[0034] The first binder preferably has, for example, [-CH2-CF2-] (hereinafter, sometimes referred to as formula 1) as a constituent unit. Furthermore, the first binder preferably has a constituent unit represented by formula 1 as the main constituent unit. "Main constituent unit" refers to the largest proportion (molar ratio) among all the constituent units constituting the binder. The proportion of the constituent unit represented by formula 1 to all the constituent units constituting the first binder is, for example, 50 mol% or more, may be 70 mol% or more, or may be 90 mol% or more.
[0035] The first binder may have, for example, [-C2F4-] (hereinafter, sometimes referred to as formula 2) as a constituent unit. Furthermore, the first binder may have a constituent unit represented by (formula 2) as the main constituent unit. The ratio of the constituent unit represented by (formula 2) to all the constituent units constituting the first binder is, for example, 50 mol% or more, may be 70 mol% or more, or may be 90 mol% or more.
[0036] The first binder may or may not have a structural unit represented by [-CF2CF(CF3)-] (hereinafter sometimes referred to as formula 3). In the former case, the first binder may have a structural unit represented by formula 1 or formula 2 and a structural unit represented by formula 3.
[0037] Other examples of the first binder include acrylic resin-based binders such as polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polypropyl acrylate, polybutyl acrylate, polyhexyl acrylate, poly2-ethylhexyl acrylate, and polydecyl acrylate; methacrylic acid resin-based binders such as polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polybutyl methacrylate, and poly2-ethylhexyl methacrylate; olefin resin-based binders such as polyethylene, polypropylene, and polystyrene; imide resin-based binders such as polyimide and polyamideimide; amide resin-based binders such as polyamide; polycarboxylic acid-based binders such as polyitaconic acid, polycrotonic acid, polyfumaric acid, polyangelic acid, and carboxymethyl cellulose; and rubber-based binders such as butadiene rubber, hydrogenated butadiene rubber, styrene butadiene rubber (SBR), hydrogenated styrene butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, and ethylene propylene rubber.
[0038] The swelling degree of the first binder is, for example, 25% or less, may be 23% or less, or may be 21% or less. In the present disclosure, the swelling degree of the binder is the weight increase rate of the binder alone when immersed in an electrolyte at 60° C. for 24 hours. It is preferable to use the same electrolyte used for measuring the swelling degree as the electrolyte constituting the battery. Typically, an electrolyte is used in which LiPF6 is dissolved to 1M in a mixed solvent containing EC:DMC:EMC=3:4:3 in a volume ratio. Details of the method for calculating the swelling degree will be described in the examples below.
[0039] The melting point of the first binder is, for example, 155° C. or more, and may be 160° C. or more. Meanwhile, the melting point of the first binder is, for example, 200° C. or less, and may be 180° C. or less, or may be 170° C. or less. The melting point of the binder is determined, for example, by differential scanning calorimetry (DSC) in accordance with the JIS K 7121 standard.
[0040] The first binder is, for example, particulate. The average particle size of the first binder is, for example, 10 nm or more and 1000 nm or less, may be 50 nm or more and 500 nm or less, or may be 100 nm or more and 300 nm or less. In the present disclosure, the average particle size can be determined by measuring the particle size of the object by SEM observation and adopting the average value. The number of samples is preferably 100 or more.
[0041] The proportion of the first binder in the first electrode layer is not particularly limited, but is, for example, 0.1% by weight or more, may be 0.5% by weight or more, or may be 1% by weight or more, while it is, for example, 15% by weight or less, may be 10% by weight or less, or may be 5% by weight or less.
[0042] (2) First active material The first electrode layer contains a first active material. The first active material may be a positive electrode active material or a negative electrode active material.
[0043] The first active material is, for example, a lithium transition metal composite oxide. The lithium transition metal composite oxide is composed of Li and M 1 (M 1 is one or more transition metals) and O. 1 Examples of the first active material include Ni, Co, Mn, Ti, V, Cr, Fe, Cu, and Zn. 1 As the transition metal, it is preferable that at least one of Ni, Co, and Mn is contained. 1 may be partially substituted with a metal (including metalloid) belonging to Groups 13 to 17 of the periodic table. A typical example of a metal belonging to Groups 13 to 17 of the periodic table is Al.
[0044] Specific examples of the first active material include rock-salt layered active materials such as LiCoO2, LiMnO2, LiNiO2, Li(Ni,Co,Mn)O2, and Li(Ni,Co,Al)O2; LiMn2O4, Li(Ni 0. 5Mn 1.5 )O4, Li4Ti5O 12 and olivine type active materials such as LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.
[0045] The first active material is, for example, particulate. The average particle size of the first active material is, for example, 1 μm or more and 50 μm or less, or may be 2 μm or more and 30 μm or less, or may be 3 μm or more and 10 μm or less. The ratio of the first active material in the first electrode layer is not particularly limited, but may be, for example, 40 wt % or more, 60 wt % or more, or 80 wt % or more.
[0046] (3) First electrode layer The first electrode layer may further contain a first conductive material. Examples of the first conductive material include carbon materials. Examples of the carbon materials include particulate carbon materials such as carbon black, and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNTs), and carbon nanofibers (CNFs). Examples of the carbon black include acetylene black (AB), ketjen black (KB), and furnace black (FB).
[0047] The ratio of the first conductive material in the first electrode layer is not particularly limited, but may be, for example, 0.5% by weight or more, or 1% by weight or more. On the other hand, the ratio of the first conductive material is, for example, 20% by weight or less, or may be 10% by weight or less. In addition, the first electrode layer usually contains an electrolyte, which will be described later.
[0048] The first electrode layer preferably contains a first composite in which a first binder and a first conductive material are dispersed on the surface of a first active material. In the first composite, the first conductive material and the first binder are attached in a dispersed state to the surface of the first active material. The first electrode layer preferably does not contain any material other than the first composite, except for the electrolyte described below. On the other hand, when the first electrode layer contains a material other than the first composite (excluding the electrolyte described below), the ratio of the material is preferably 5% by weight or less, more preferably 1% by weight or less. Examples of materials other than the composite include an additional conductive material and an additional binder. These materials are the same as the conductive material and binder described above. In addition, the first composite is usually in a particulate form.
[0049] The thickness of the first electrode layer is, for example, 1 μm or more and 500 μm or less, or may be 5 μm or more and 250 μm or less, or may be 15 μm or more and 150 μm or less.
[0050] 2.Second electrode layer The second electrode layer is disposed on the surface of the first electrode layer opposite the current collector, and has a second active material and a second binder that coats a surface of the second active material.
[0051] (1) Second binder The second electrode layer contains a second binder. The second binder is usually a polymer. Details of the second binder are the same as those of the first binder described above, so the description here is omitted.
[0052] The second binder and the first binder may have the same composition or different compositions. In particular, it is preferable that the second binder and the first binder have the same composition. This is because the swelling degree of the second binder and the first binder is the same, and therefore stress is less likely to occur between the second electrode layer and the first electrode layer when the binder swells with the electrolytic solution.
[0053] The ratio of the second binder in the second electrode layer is not particularly limited, but may be, for example, 0.1% by weight or more, 0.5% by weight or more, or 1% by weight or more. On the other hand, it may be, for example, 15% by weight or less, 10% by weight or less, or 5% by weight or less. In addition, it is preferable that the ratio B2 (weight %) of the second binder in the second electrode layer is the same as the ratio B1 (weight %) of the first binder in the first electrode layer. The ratio B2 and the ratio B1 being the same means that the absolute value of the difference between the two is 0.5% by weight or less. On the other hand, the ratio B2 may be larger than the ratio B1, or may be smaller than the ratio B1.
[0054] (2)Second active material The second electrode layer contains a second active material. The second active material may be a positive electrode active material or a negative electrode active material. The second active material and the first active material usually function as active materials having the same polarity. Details of the second active material are the same as those of the first active material described above, so the description here is omitted.
[0055] The second active material and the first active material may have the same composition or different compositions. In particular, it is preferable that the second active material and the first active material have the same composition, because the charge / discharge behavior is the same and voltage control is easy.
[0056] The proportion of the second active material in the second electrode layer is not particularly limited, but may be, for example, 40% by weight or more, 60% by weight or more, or 80% by weight or more. The proportion A2 (% by weight) of the second active material in the second electrode layer is preferably the same as the proportion A1 (% by weight) of the first active material in the first electrode layer. The proportion A2 and the proportion A1 being the same means that the absolute value of the difference between the two is 5% by weight or less. On the other hand, the proportion A2 may be larger than the proportion A1, or may be smaller than the proportion A1.
[0057] (3) Second electrode layer The second electrode layer may further contain a second conductive material. Details of the second conductive material are the same as those of the first conductive material described above, and therefore will not be described here.
[0058] The ratio of the second conductive material in the second electrode layer is not particularly limited, but may be, for example, 0.5% by weight or more, and may be 1% by weight or more. On the other hand, the ratio of the second conductive material is, for example, 20% by weight or less, and may be 10% by weight or less. In addition, it is preferable that the ratio E2 (weight %) of the second conductive material in the second electrode layer is the same as the ratio E1 (weight %) of the first conductive material in the first electrode layer. The ratio E2 and the ratio E1 being the same means that the absolute value of the difference between the two is 0.5% by weight or less. On the other hand, the ratio E2 may be larger than the ratio E1, or may be smaller than the ratio E1. In addition, the second electrode layer usually contains an electrolyte, which will be described later.
[0059] The second electrode layer preferably contains a second composite in which a second binder and a second conductive material are dispersed on the surface of the second active material. In the second composite, the second conductive material and the second binder are attached in a dispersed state to the surface of the second active material. The second electrode layer preferably does not contain any material other than the second composite, except for the electrolyte described below. On the other hand, when the second electrode layer contains a material other than the second composite (excluding the electrolyte described below), the ratio of the material is preferably 5% by weight or less, more preferably 1% by weight or less. Examples of the material other than the second composite include an additional conductive material and an additional binder. The second composite is usually in a particulate form.
[0060] The thickness of the second electrode layer is, for example, 1 μm or more and 500 μm or less, or may be 5 μm or more and 250 μm or less, or may be 15 μm or more and 150 μm or less.
[0061] The relationship between the thickness of the second electrode layer and the thickness of the first electrode layer is not particularly limited. The thickness of the second electrode layer may be greater than the thickness of the first electrode layer, may be the same as the thickness of the first electrode layer, or may be smaller than the thickness of the first electrode layer. "The thickness of the second electrode layer and the thickness of the first electrode layer are the same" means that the absolute value of the difference between the thicknesses of the two is 3 μm or less.
[0062] The thickness of the first electrode layer is T1, and the thickness of the second electrode layer is T2. The ratio of T1 to the sum of T1 and T2 (T1 / (T1+T2)) is, for example, 30% or more, or may be 40% or more, or may be 45% or more. Within the above range, the decrease in the capacity retention rate during high-temperature storage can be further suppressed. The ratio (T1 / (T1+T2)) is, for example, 70% or less, or may be 60% or less, or may be 55% or less. Within the above range, the increase in the resistance increase rate during high-temperature storage can be further suppressed.
[0063] 3. Current collector The current collector in the present disclosure collects the current from the first electrode layer and the second electrode layer. The current collector may be a positive electrode current collector or a negative electrode current collector. Examples of the material of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. Examples of the material of the negative electrode current collector include SUS, copper, nickel, and carbon. Examples of the shape of the current collector include a foil shape and a mesh shape.
[0064] 4.Electrode The electrode in the present disclosure has a current collector, a first electrode layer, and a second electrode layer in this order in the thickness direction. The electrode in the present disclosure is used in a battery. FIG. 2(a) is a schematic plan view illustrating the electrode in the present disclosure, and FIG. 2(b) is a cross-sectional view taken along line AA in FIG. 2(a). As shown in FIGS. 2(a) and (b), the stacking direction D of the electrode 10 is L In a plan view from the top, the area of the current collector 1 is preferably larger than the area of the first electrode layer 2a. The area of the first electrode layer 2a is preferably larger than the area of the second electrode layer 2b. That is, in the stacking direction D of the electrode 10, LFrom this viewpoint, when the areas of the current collector 1, the first electrode layer 2a and the second electrode layer 2b are S0, S1 and S2, respectively, it is preferable that S0>S1>S2.
[0065] As shown in FIG. 2(a) and (b), the stacking direction D of the electrode 10 L When viewed from the top, the entire periphery of the first electrode layer 2a is preferably located inside the entire periphery of the current collector 1 (positional relationship A). L When viewed from the stacking direction of the electrodes, it is preferable that the entire outer periphery of the second electrode layer 2b is located inside the entire outer periphery of the first electrode layer 2a (positional relationship B). When pressing the current collector, the first electrode layer, and the second electrode layer, when viewed from the stacking direction of the electrodes, pressure is likely to escape at the boundary between the current collector and the first electrode layer and the boundary between the first electrode layer and the second electrode layer, and peeling is likely to occur when the binder swells. In contrast, by satisfying positional relationship A and positional relationship B, pressure is less likely to escape and peeling is less likely to occur when the binder swells. As a result, the capacity retention rate is improved.
[0066] B.Battery Fig. 3 is a schematic cross-sectional view illustrating a battery according to the present disclosure. The battery 20 shown in Fig. 3 has a positive electrode 13 having a positive electrode current collector 11 and a positive electrode layer 12, a negative electrode 16 having a negative electrode current collector 14 and a negative electrode layer 15, and an electrolyte layer 17 disposed between the positive electrode 13 and the negative electrode 16. At least one of the positive electrode 13 and the negative electrode 16 corresponds to the electrode described in "A. Electrode" above.
[0067] According to the present disclosure, at least one of the positive electrode and the negative electrode is the above-mentioned electrode, so that during high-temperature storage, it is possible to suppress an increase in the resistance increase rate while suppressing a decrease in the capacity retention rate.
[0068] 1. Positive electrode The positive electrode has a positive electrode current collector and a positive electrode layer disposed on the electrolyte layer side of the positive electrode current collector. The positive electrode in the present disclosure preferably corresponds to the above-mentioned electrode. On the other hand, when the positive electrode in the present disclosure does not correspond to the above-mentioned electrode, the negative electrode in the present disclosure usually corresponds to the above-mentioned electrode. In this case, any conventional positive electrode can be used as the positive electrode.
[0069] 2.Negative electrode The negative electrode has a negative electrode current collector and a negative electrode layer disposed on the surface of the negative electrode current collector on the electrolyte layer side. The negative electrode in the present disclosure preferably corresponds to the above-mentioned electrode. On the other hand, when the negative electrode in the present disclosure does not correspond to the above-mentioned electrode, the positive electrode in the present disclosure usually corresponds to the above-mentioned electrode. In this case, any conventional negative electrode can be used as the negative electrode.
[0070] 3. Electrolyte layer The electrolyte layer in the present disclosure contains at least an electrolyte, such as a liquid electrolyte (electrolytic solution) or a gel electrolyte.
[0071] The electrolyte solution contains, for example, a lithium salt and a solvent. Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6; and organic lithium salts such as LiCF3SO3, LiN(SO2CF3)2, LiN(SO2C2F5)2, and LiC(SO2CF3)3. Examples of the solvent include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The solvent may be one type only, or two or more types.
[0072] The gel electrolyte is usually obtained by adding a polymer to an electrolytic solution. Examples of the polymer include polyethylene oxide and polypropylene oxide. The thickness of the electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less. The electrolyte layer may have a separator.
[0073] 4.Battery The battery in the present disclosure is typically a lithium-ion secondary battery. Examples of uses of the battery include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, the battery in the present disclosure is preferably a power source for driving vehicles. The battery in the present disclosure may also be used as a power source for moving objects other than vehicles (e.g., railways, ships, and aircraft), and may also be used as a power source for electrical products such as information processing devices.
[0074] C. Electrode manufacturing method 4 is a flow diagram illustrating a method for manufacturing an electrode according to the present disclosure. First, a first electrode layer is formed on a current collector by a dry method using a first electrode mixture containing a first active material and a first binder that covers the surface of the first active material (first film formation step, S1). Next, a second electrode layer is formed on the first electrode layer by a dry method using a second electrode mixture containing a second active material and a second binder that covers the surface of the second active material (second film formation step, S2). The coverage C1 of the first binder with respect to the first active material is greater than the coverage C2 of the second binder with respect to the second active material.
[0075] 1.First film formation process The first film-forming step in the present disclosure is a step of forming a first electrode layer on a current collector by a dry method using a first electrode mixture containing a first active material and a first binder that coats the surface of the first active material. In the present disclosure, the dry method refers to a method of forming an electrode layer without using a dispersion medium such as an organic solvent.
[0076] The first electrode mixture contains a first active material and a first binder that coats the surface of the first active material. The first electrode mixture preferably further contains a first conductive material. In particular, the first electrode mixture preferably contains a first composite in which the first binder and the first conductive material are dispersed on the surface of the first active material.
[0077] The method for producing the first composite includes a method of subjecting the first active material, the first binder, and the first conductive material to a composite treatment device. The composite treatment is preferably performed in a dry manner. Examples of the composite treatment device include a mixer, a bead mill, a ball mill, and a mortar. When the composite treatment is performed using a mixer, the rotation speed during the composite treatment (under load) is, for example, 500 rpm or more and 20,000 rpm or less, and may be 1,000 rpm or more and 10,000 rpm or less. The treatment time is, for example, 30 seconds or more and 2 hours or less, and may be 1 minute or more and 1 hour or less, or may be 1 minute or more and 30 minutes or less.
[0078] It is preferable that the first electrode mixture does not contain any material other than the first composite. On the other hand, when the first electrode mixture contains a material other than the first composite, the ratio of the material is preferably 5% by weight or less, more preferably 1% by weight or less. Examples of the material other than the first composite include an additional conductive material and an additional binder. The additional conductive material and the additional binder are the same as those described in "A. Electrode" above.
[0079] In the present disclosure, the first electrode layer is formed on the current collector by a dry method using the first electrode composite material. By forming the first electrode layer by a dry method, it is possible to reduce the drying time and the amount of organic solvent used. An example of the dry method is an electrostatic film formation method such as electrostatic screen film formation. After forming the first electrode layer on the current collector, it may be heated to increase the binding property or pressed to increase the composite density, if necessary. The current collector is the same as described above in "A. Electrode".
[0080] 2.Second film formation process The second film-forming process in the present disclosure is a process of forming a second electrode layer on the first electrode layer by a dry method using a second electrode mixture containing a second active material and a second binder that coats the surface of the second active material.
[0081] The second electrode mixture contains a second active material and a second binder that coats the surface of the second active material. The second electrode mixture preferably further contains a second conductive material. In particular, the second electrode mixture preferably contains a second composite in which the second binder and the second conductive material are dispersed on the surface of the second active material. The method for producing the second composite is the same as the method for producing the first composite described above.
[0082] The second electrode mixture preferably does not contain any material other than the second composite. On the other hand, when the second electrode mixture contains a material other than the second composite, the ratio of the material is preferably 5% by weight or less, more preferably 1% by weight or less. Examples of the material other than the second composite include an additional conductive material and an additional binder. The additional conductive material and the additional binder are the same as those described in "A. Electrode" above.
[0083] In the present disclosure, the second electrode layer is formed on the first electrode layer by a dry method using the second electrode composite. By forming the second electrode layer by a dry method, it is possible to reduce the drying time and the amount of organic solvent used. As the dry method, for example, an electrostatic film formation method such as electrostatic screen film formation can be mentioned. After forming the second electrode layer on the first electrode layer, it may be heated to increase the binding property or pressed to increase the composite density, if necessary.
[0084] 3. Electrode The electrodes obtained by the first and second film-forming steps are the same as those described in "A. Electrode" above.
[0085] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0086] [Comparative Example 1] First, a positive electrode active material (NCM, particle size 3 to 10 μm, manufactured by Sumitomo Metal Mining Co., Ltd.), a conductive material (acetylene black (Li400, manufactured by Denka Co., Ltd.) and a binder (#7300 (polyvinylidene fluoride), manufactured by Kureha Corporation) were weighed and mixed in a ratio of positive electrode active material:conductive material:binder = 97.5 / 1.5 / 1 (wt%). A dispersion medium was added to the obtained mixture and stirred to obtain a positive electrode slurry. The obtained positive electrode slurry was applied onto a positive electrode current collector (aluminum foil with a thickness of 12 μm) using a film applicator, and then dried at 80 ° C. for 5 minutes. As a result, a positive electrode structure having a positive electrode current collector and a positive electrode layer was obtained.
[0087] Next, the negative electrode active material (natural graphite) and the binder (SBR and CMC) were mixed, and a dispersion medium was added to the resulting mixture, followed by stirring to obtain a negative electrode slurry. The resulting negative electrode slurry was applied onto a negative electrode current collector using a film applicator, and then dried at 80°C for 5 minutes. This resulted in a negative electrode structure having a negative electrode current collector and a negative electrode layer.
[0088] The positive electrode layer of the positive electrode structure and the negative electrode layer of the negative electrode structure were placed opposite each other with a separator interposed between them, wound, and an electrolyte was injected to obtain an evaluation cell. The electrolyte used was a mixed solvent containing EC, DMC, and EMC in a volume ratio of EC:DMC:EMC=3:4:3, with LiPF6 dissolved to a concentration of 1M.
[0089] [Comparative Example 2] (1) Composite cathode materials First, a positive electrode active material (NCM, particle size 3 to 10 μm, manufactured by Sumitomo Metal Mining Co., Ltd.), a conductive material (acetylene black (Li400, manufactured by Denka Co., Ltd.) and a binder (HSV1810 (polyvinylidene fluoride), particle size 150 nm, manufactured by Arkema) were weighed out in a ratio of positive electrode active material:conductive material:binder = 97.5:1.5:1 (wt%) and charged into an MP mixer manufactured by Nippon Coke and Engineering Co., Ltd., and stirred at 10,000 rpm for 10 minutes to perform a composite treatment, thereby obtaining a composite (composite A).
[0090] (2) Film formation The obtained composite was dry-coated on a current collector (aluminum foil having a thickness of 12 μm) using an electrostatic screen film-forming machine (Belk Kogyo Co., Ltd.) at a voltage of 1.5 kV and a distance of 1 cm between the current collector and the screen.
[0091] (3) Establishment A load of 5 tons was applied for 1 minute between flat plates heated to 180°C on both sides, softening (melting) the binder and fixing the composite to the current collector, producing a positive electrode structure having a positive electrode current collector and a positive electrode layer.
[0092] (4) Preparation of evaluation cells An evaluation cell was obtained in the same manner as in Comparative Example 1, except that the obtained positive electrode structure was used.
[0093] [Comparative Example 3] Except for changing the stirring time in the composite treatment to 60 minutes, a composite (composite B) was obtained in the same manner as in Comparative Example 2. Except for using the obtained composite, an evaluation cell was obtained in the same manner as in Comparative Example 2.
[0094] [Example 1] Composite A was prepared in the same manner as in Comparative Example 2, and composite B was prepared in the same manner as in Comparative Example 3. The obtained composite B was dry-coated on a current collector (aluminum foil having a thickness of 12 μm) using an electrostatic screen film-forming machine (Berg Kogyo) to form a first electrode layer (lower layer). At this time, the voltage was 1.5 kV, and the distance between the current collector and the screen was 1 cm. Next, composite A was dry-coated on the first electrode layer under the same conditions to form a second electrode layer (upper layer).
[0095] Thereafter, a load of 5 t was applied for 1 minute by using flat plates heated to 180°C on both sides to soften (melt) the binder, and composite A was fixed to the current collector, producing a positive electrode structure having a positive electrode collector, a first positive electrode layer (first electrode layer) formed on the positive electrode collector, and a second positive electrode layer (second electrode layer) formed on the first positive electrode layer. An evaluation cell was obtained in the same manner as in Comparative Example 1, except that the obtained positive electrode structure was used.
[0096] [evaluation] (1) Swelling degree The swelling degree of the binder used in Comparative Example 1 (wet type) and Comparative Example 2 (dry type) was measured. Specifically, the weight of the binder processed into a sheet shape (weight of the binder before immersion) was measured, and the binder was immersed in an electrolyte solution at 60°C (a mixed solvent containing EC:DMC:EMC=3:4:3 in a volume ratio, with LiPF6 dissolved to 1M) for 24 hours. Next, the weight of the binder removed from the electrolyte solution (weight of the binder after immersion) was measured, and the swelling degree of the binder was calculated by the following formula. Swelling degree of binder (%)=((weight of binder after immersion)-(weight of binder before immersion)) / (weight of binder before immersion)×100 As a result, the swelling degree of the binder used in Comparative Example 1 (wet type) was 15%, and the swelling degree of the binder used in Example 1 (dry type) was 21%.
[0097] (2) Melting point The melting points of the binders used in Comparative Example 1 (wet type) and Comparative Example 2 (dry type) were measured. Specifically, they were determined by differential scanning calorimetry (DSC) in accordance with the provisions of JIS K 7121. As a result, the melting point of the binder used in Comparative Example 1 (wet type) was 173°C, and the melting point of the binder used in Comparative Example 2 (dry type) was 167°C.
[0098] (3) Coverage The composites obtained in Comparative Example 2 and Comparative Example 3 were observed with a SEM (scanning electron microscope), and binarized to calculate the coverage of the binder. Specifically, as shown in FIG. 5, the composites were observed with a SEM and binarized. In the binarization, a threshold was set using Otsu's binarization method. Since a conductive material (acetylene black) adheres to the binder-covered area on the surface of the active material, the ratio of black to the whole in the image after binarization was taken as the coverage of the binder. The results are shown in Table 1.
[0099] (4) Capacity maintenance rate The capacity retention rates before and after the high-temperature test were determined for the evaluation cells obtained in Comparative Examples 1 to 3 and Example 1. Specifically, the evaluation cells were charged and discharged to determine the capacity (initial capacity). Next, the evaluation cells were stored in a thermostatic chamber at 60°C for 10 days, and the capacity (capacity after storage) of the evaluation cells was measured in the same manner. The capacity retention rate was determined by the following formula. The results are shown in Table 1. Capacity retention rate (%) = (Capacity after storage / Initial capacity) × 100
[0100] (5)Rate of increase in resistance The resistance increase rate before and after the high-temperature test was determined for the evaluation cells obtained in Comparative Examples 1 to 3 and Example 1. Specifically, after charging the evaluation cell, it was discharged for 10 seconds at currents I of 0.3C, 0.5C, and 1C, and the voltage drop ΔV during the 10 seconds was measured. The IV resistance (initial resistance) was determined from the relationship between the current I and ΔV. Next, the evaluation cell was stored in a thermostatic chamber at 60°C for 10 days, and the IV resistance (resistance after storage) of the evaluation cell was determined in the same manner. The resistance increase rate was determined by the following formula. The results are shown in Table 1. Resistance increase rate (%) = (resistance after storage / initial resistance) x 100
[0101] [Table 1]
[0102] As shown in Table 1, Comparative Example 2 had a lower capacity retention rate than Comparative Example 1, but a reduced resistance increase rate was confirmed. The binder used in Comparative Example 2 (dry type) has a lower melting point (higher swelling degree) than the binder used in Comparative Example 1 (wet type) in order to improve the coverage rate. Therefore, Comparative Example 2 is more susceptible to the binder swelling caused by the electrolyte than Comparative Example 1, which is thought to have resulted in a lower capacity retention rate than Comparative Example 1. On the other hand, a composite treatment was performed in Comparative Example 2, and the coverage rate of the binder in Comparative Example 2 was higher than that of the binder in Comparative Example 1, which is thought to have suppressed the increase in resistance due to binder swelling.
[0103] As shown in Table 1, Comparative Example 3 had a higher capacity retention rate than Comparative Example 2, but an increase in the resistance increase rate was confirmed. Comparative Example 3 had a higher binder coverage rate than Comparative Example 2, and therefore had a higher binding strength in the electrode layer. This is believed to have allowed the binding strength to be maintained even after the binder swelled by the electrolyte, resulting in a higher capacity retention rate. On the other hand, Comparative Example 3 had a higher binder coverage rate than Comparative Example 2, and therefore is believed to have increased the resistance increase rate during high-temperature storage (when the binder swells).
[0104] In contrast, as shown in Table 1, in Example 1, the capacity retention rate was higher than in Comparative Example 2, and the resistance increase rate was lower than in Comparative Example 3. In other words, both an improvement in the capacity retention rate and a suppression of the resistance increase rate were achieved. This is presumably because the coverage rate of the binder in the first electrode layer (lower layer) was relatively high, making it difficult for the first electrode layer to peel off from the current collector, thereby improving the capacity retention rate, and at the same time, the coverage rate of the binder in the second electrode layer (upper layer) was relatively low, suppressing the resistance increase rate during high-temperature storage (when the binder swells).
[0105] [Reference example] The stirring time in the composite treatment was adjusted to prepare four composites (composites A to D) with different coverage rates. The composites A and B were the same as the composites A and B prepared in the above-mentioned Comparative Examples 2 and 3, respectively. The powder resistivity of the obtained composites A to D was measured using an automatic powder resistivity measurement system, low resistance version MCP-PD600. The results are shown in FIG. 6. As shown in FIG. 6, it was confirmed that the powder resistivity significantly decreased when the coverage rate of the binder was 50% or less. Therefore, it was confirmed that the coverage rate C2 of the second binder with respect to the second active material is preferably 50% or less. [Explanation of symbols]
[0106] 1...Current collector 2a...first electrode layer 2b...Second electrode layer 10...Electrode 11...Positive electrode current collector 12...Positive electrode layer 13...Positive electrode 14... Negative electrode current collector 15... Negative electrode layer 16... Negative electrode 17... Electrolyte layer 20... Battery
Claims
1. An electrode for use in a battery, comprising: the electrode includes a current collector, a first electrode layer disposed on the current collector, and a second electrode layer disposed on the first electrode layer; the first electrode layer has a first active material and a first binder that coats a surface of the first active material, the second electrode layer has a second active material and a second binder that coats a surface of the second active material, The coverage of the first binder with respect to the first active material is C 1 (%), and the coverage of the second binder with respect to the second active material is C 2 (%), the C 1 is the above C 2 Bigger, electrode.
2. Said C 1 is greater than 50%, and 2 2. The electrode of claim 1, wherein the .lambda.
3. Said C 1 and the above C 2 The electrode according to claim 1 , wherein the difference between the first and second electrodes is 30% or more.
4. The electrode of claim 1 , wherein the first binder and the second binder are fluorine-containing binders.
5. The electrode of claim 1 , wherein the first binder and the second binder have the same composition.
6. 2. The electrode of claim 1, wherein the first active material and the second active material are a lithium transition metal composite oxide.
7. The electrode of claim 1 , wherein the first active material and the second active material have the same composition.
8. the first electrode layer contains a first composite in which the first binder and a first conductive material are dispersed on a surface of the first active material, 2. The electrode of claim 1, wherein the second electrode layer comprises a second composite having the second binder and a second conductive material dispersed on a surface of the second active material.
9. A battery having a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode, A battery, wherein at least one of the positive electrode and the negative electrode is an electrode according to any one of claims 1 to 8.
10. 10. The battery of claim 9, wherein the battery is a lithium ion battery.
11. A method for producing an electrode for use in a battery, comprising the steps of: a first film-forming step of forming a first electrode layer on a current collector by a dry method using a first electrode mixture containing a first active material and a first binder that coats a surface of the first active material; a second film-forming step of forming a second electrode layer on the first electrode layer by a dry method using a second electrode mixture containing a second active material and a second binder that coats a surface of the second active material; having The coverage of the first binder with respect to the first active material is C 1 (%), and the coverage of the second binder with respect to the second active material is C 2 (%), the C 1 is the above C 2 Larger, a method for manufacturing electrodes.
Citation Information
Patent Citations
Electrode for nonaqueous electrolyte secondary battery and its manufacture
JP1997185960A
Electrode for nonaqueous electrolyte secondary battery and its manufacture
JP1998270013A
Multilayer electrode structure, battery using the same, electrical double layer capacitor, and their manufacturing methods
JP2001307716A
Nonaqueous electrolyte secondary battery
JP2013191415A
Manufacturing method of electrode for secondary battery and manufacturing method of the secondary battery
JP2019096501A